Drain, connect, and cultivate. Contributions to the study of agribusiness expansion in the Southern Lowlands, Argentina (Huellas, 2026)
The current water and environmental crisis affecting Latin America, and Argentina in particular, is reflected not only in changes in water availability, loss of biodiversity and an increase in extreme weather events, but also in a profound transformation of rural areas. This process, far from being natural or inevitable, must be understood within the framework of the logic of capital—immersed in an evident metabolic collapse—and the spatial restructuring driven by agribusiness, especially in its most recent phase of expansion into new productive frontiers, generating changes in land use patterns. Among these changes, the Bajos Submeridionales—a vast region of wetlands covering areas of northern Santa Fe, southern Chaco, and northeastern Santiago del Estero—have become the target of intervention by state and private projects seeking to ‘enhance’ their productive value. In this paper, we will address the transformations that have taken place in one of Argentina's largest wetlands, which are reconfiguring socio-territorial relationships and ways of life, based on the development of what we consider to be the three engineering disciplines of agribusiness.